The Principle of Self-Determination in the Context of Human Rights - Gadkowski, Tadeusz (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2017)
The essay presents the issue of the principle of self-determination from the perspective of international human rights law. The author highlights the close relationship between the principle of self-determination and the principle of respect for human rights and fundamental freedoms. In practice, the principle of self-determination is a prerequisite for the effective guarantee of human rights, and, at the same time, guaranteed protection of human rights is a prerequisite for implementing the principle of national self determination. The author presents the issue of self-determination in the context of the basic regulations of international human rights law, considering regulations of both a ‘hard’ and ‘soft’ law character.